INTEGRASI ILMU PENGETAHUAN DAN AGAMA DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM - Siti Khumairah; Mumun; Latifah (Yayasan Pendidikan Literasi Borneo, 2025)
The integration of science and religion has become a key issue in the development of Islamic Education (PAI) curriculum in higher education. This integration aims to eliminate the dichotomy between religious knowledge and secular sciences, enabling Islamic understanding to be not only theological but also compatible with modern scientific developments. This study aims to analyze the concept of science–religion integration in PAI curricula, its implementation, and the challenges encountered by higher education institutions. The research approach is qualitative, employing a literature-based analysis from relevant scholarly sources. The findings reveal that integration can be strengthened through holistic paradigms, value-based curriculum design, and the use of scientific knowledge as an instrument to reinforce Islamic teachings. Implementation strategies include interdisciplinary learning, contextual teaching, and content delivery aligned with technological advancements. The integration significantly contributes to character formation, enhancement of religious literacy, and students’ adaptive abilities in facing global challenges. However, major obstacles include existing dichotomous thinking, limited interdisciplinary lecturer competencies, and weak synergy between religious and secular academic institutions. Therefore, universities need to design innovative and collaborative PAI curricula that respond to the dynamics of scientific development.